1997
DOI: 10.1007/s11661-997-0283-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling charpy impact energy property changes using a bayesian method

Abstract: Surveillance schemes that monitor the effect of neutron irradiation on reactor pressure vessel materials employ Charpy impact specimens that are periodically withdrawn and tested as a function of test temperature. The resulting Charpy impact absorbed energy curves have been modeled by a threeparameter relationship with the same functional form as the Burr distribution function. The parameters of the Burr distribution function have been represented as a function of irradiation variables: dose and temperature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 3 publications
0
25
0
1
Order By: Relevance
“…The toughness of steels is often predicted by a simplified semi-empirical formula obtained from the correlation of fracture speed with crack propagation speed [9,10]. In the case of the high-strength steels such as tempered martensitic steels, however, the correlation of Charpy USE with fundamental fracture process or crack speed is less obvious [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The toughness of steels is often predicted by a simplified semi-empirical formula obtained from the correlation of fracture speed with crack propagation speed [9,10]. In the case of the high-strength steels such as tempered martensitic steels, however, the correlation of Charpy USE with fundamental fracture process or crack speed is less obvious [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Windle and co-workers [5] used a Burr distribution function to describe these data. Here, the variation of Charpy impact energy, C , with test temperature T i is given by:…”
Section: Stage 2: Analysis Of Irradiated Charpy Impact Energy Datamentioning
confidence: 99%
“…When testing several, nominally identical samples, it is commonly observed that in the transition region, the absorbed energy values are largely scattered [4] whereas different plateau values, brittle (lower shelf) and ductile (upper shelf), are obtained from dynamic or static mechanical tests [5]. Moreover, this dispersion is characteristic of all the kinds of experimental determinations of the fracture toughness whereas for a given material T DBT values are sample-size dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Macroscopic modeling of the impact test has been devoted to the derivation of reasonable forms for fitting the experimental results and for obtaining estimates of models parameters and of the associated standard errors [4,6,7]. However, no generally accepted distribution function has been proposed accounting for the variability in the proportions of brittle and ductile fracture stemming from the dispersion in the microstructures of the samples.…”
Section: Introductionmentioning
confidence: 99%